Laryngeal Tuberculosis: an uncommon but important cause of odynophagia - Agarwal, Abhishek; Khan, Asna; Pandey, Saurav; Vaish, Arvind Kumar (International Journal of Advances in Medicine, 2017)
Tuberculosis can occur as pulmonary tuberculosis or as extrapulmonary tuberculosis. The commonest forms of extrapulmonary tuberculosis include the pleural tuberculosis and the lymph node tuberculosis. Here we are describing an interesting case of laryngeal tuberculosis which presented to us with odynophagia. The diagnosis was suspected on basis of chest x-ray and CT thorax, but it could only be confirmed after direct visualization of the larynx on fibreoptic bronchoscopy and by taking biopsy from the epiglottis under direct visualization.